2002
DOI: 10.1046/j.1528-1157.2002.33800.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Lobe Epilepsy Surgery: Outcome, Complications, and Late Mortality Rate in 215 Patients

Abstract: Summary: Purpose:We studied the surgical outcome, complications, and the late mortality rate in a large group of patients with medically refractory temporal lobe epilepsy (TLE).Methods: Two-hundred fifteen patients with TLE were treated surgically between 1984 and 1999 after a comprehensive presurgical evaluation. Patients were followed up at 6 weeks, 3-6 months, and yearly thereafter. In addition, questionnaires were sent on the anniversary of their surgery. Surgical outcome (Engel's classification), complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
2
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(115 citation statements)
references
References 12 publications
11
94
2
8
Order By: Relevance
“…12 Salanova et al demonstrated that people who continued to have seizures after surgery had a SMR of 7.4 in contrast to those who were seizure free postsurgery (SMR=1.7); 2/11 deaths were due to suicide. 13 Likewise, Hennessy et al demonstrated that overall post surgical patients had higher mortality rate compared to the general population (SMR=4.5). 8 One of their 20 deaths were due to suicide in a subject who had post-surgical depression but was seizure free.…”
Section: Resultsmentioning
confidence: 97%
“…12 Salanova et al demonstrated that people who continued to have seizures after surgery had a SMR of 7.4 in contrast to those who were seizure free postsurgery (SMR=1.7); 2/11 deaths were due to suicide. 13 Likewise, Hennessy et al demonstrated that overall post surgical patients had higher mortality rate compared to the general population (SMR=4.5). 8 One of their 20 deaths were due to suicide in a subject who had post-surgical depression but was seizure free.…”
Section: Resultsmentioning
confidence: 97%
“…Evaluation of 215 patients with temporal lobe epilepsy found 3 of 148 (2%) seizure-free patients died after surgery, compared with 8 of 67 (11.9%) non-seizure-free patients. 26) In a series of 583 patients who underwent epilepsy surgery, only one of 258 (0.4%) patients with no recurrent seizure died, whereas 18 of 325 (5.5%) patients with recurrent seizure died. 29) These findings suggest that mortality after epilepsy surgery is associated with seizure persistence and successful surgery reduces the mortality rate among patients with MTLE.…”
Section: Discussionmentioning
confidence: 99%
“…27,33) Resective surgery for MTLE has shown favorable outcome and safety, but is not free from failure of seizure control, morbidity, and relapse of seizure. 1,23,26,28,32) Given such faults of conventional surgery, other treatment options should be developed with better outcome and lower morbidity than open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala and hippocampus are excised en bloc. Ninety percent seizure free results are expected [5].…”
Section: Resectionsmentioning
confidence: 96%